Structured Teacher–Child Questioning for Oral Language Participation in Rural Indonesian Early Childhood Education: Baseline Findings and an Action-Research Protocol - Nuzul Fania; Jamilah; Fiqi Nurmanda Sari; Husin (Women, Education, and Social Welfare, 2026)
Oral language is central to young children’s participation, learning, and later educational opportunity. This study reports the baseline stage of a planned classroom action research project examining structured teacher–child questioning in a rural Indonesian early childhood education and care (ECEC) center. Aggregate baseline records for 15 children aged 5–6 years were analyzed descriptively. Seven children (46.7%) were classified as Not Yet Developing, six (40.0%) as Emerging, two (13.3%) as Developing as Expected, and none as Very Well Developed in the center’s existing language-development framework. Eight children were reported to experience participation barriers, including delayed responses to educator questions (n = 5), unclear speech articulation (n = 2), and limited spontaneous verbal initiation (n = 1). The manuscript translates these findings into a two-cycle questioning protocol that prioritizes open prompts, wait time, contingent expansion, peer uptake, and brief observation records. The contribution is an equity-oriented framework for widening oral-language participation in rural ECEC, rather than a claim of intervention efficacy. Because no Cycle I or Cycle II outcome data were available in the source records, causal improvement is not inferred. Future implementation should report child-level, de-identified trajectories, intervention fidelity, and safeguarding procedures.